2013
DOI: 10.1017/s0022029913000277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farming strategies on environmental impact of intensive dairy farms in Italy

Abstract: Agriculture and animal husbandry are important contributors to global emissions of greenhouse (GHG) and acidifying gases. Moreover, they contribute to water pollution and to consumption of non-renewable natural resources such as land and energy. The Life Cycle Assessment (LCA) methodology allows evaluation of the environmental impact of a process from the production of inputs to the final product and to assess simultaneously several environmental impact categories among which GHG emissions, acidification, eutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 24 publications
(51 reference statements)
5
32
2
15
Order By: Relevance
“…About the environmental impact aspects, the values of GWP reported are similar to what was found in a previous study in the same region by Guerci et al (2013) in intensive dairy farms, while the same authors found values of acidification and eutrophication higher than those reported in this study; this result is due to the different kind of farms included in the present study: some were intensive farms, with large use of fertilisers and high stocking density (LU/ha of land), some used small amounts of fertiliser and the number of animals per hectare was limited. Land use and eutrophication resulted higher than the findings of Meul et al (2014).…”
Section: Thresholds Of Multi-dimensional Assessmentsupporting
confidence: 78%
See 1 more Smart Citation
“…About the environmental impact aspects, the values of GWP reported are similar to what was found in a previous study in the same region by Guerci et al (2013) in intensive dairy farms, while the same authors found values of acidification and eutrophication higher than those reported in this study; this result is due to the different kind of farms included in the present study: some were intensive farms, with large use of fertilisers and high stocking density (LU/ha of land), some used small amounts of fertiliser and the number of animals per hectare was limited. Land use and eutrophication resulted higher than the findings of Meul et al (2014).…”
Section: Thresholds Of Multi-dimensional Assessmentsupporting
confidence: 78%
“…The environmental sustainability of animal products is of great concern worldwide; many studies were carried out in order to calculate the environmental impact of milk production in Italy (Guerci et al 2013;Bava et al 2014;Pirlo et al 2014) and in other countries (Del Prado et al 2013;Roer et al 2013). The Life Cycle Assessment (LCA) is the most frequently used method to assess environmental sustainability throughout the estimation of different environmental impact categories.…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, our work highlights (i) the synergies that exist in the promotion of farm global environmental and economic performance and (ii) the trade-offs that are present in the enhancement of farm global and local environmental performance. Our findings regarding the trade-offs between local and global environmental performance are in line with those of Guerci et al [38] and Battini et al [16], who stressed for Italian dairy farms the potential trade-offs that may exist between global and local environmental impacts.…”
Section: Discussion Of the Main Findingssupporting
confidence: 80%
“…The main focus of intensive systems is to ensure greater efficiency of production and a parallel reduction of environmental impacts (Guerci et al, 2013a). To meet these purposes, the concept of precision livestock farming (Auernhammer, 2001;Wang, 2001;Zhang et al, 2002) has been proposed.…”
Section: Ability To Function So That It Can Fulfill -Today and In Thmentioning
confidence: 99%